2014
DOI: 10.1111/wrr.12177
|View full text |Cite
|
Sign up to set email alerts
|

Genetic strain differences in the development of peritoneal fibroproliferative processes in mice

Abstract: Fibroproliferative processes are regulated by a wide variety of tissue components and genetic factors. However, whether there are genetic differences in peritoneal fibroproliferative tissue formation, with consequent differences in response to drug treatment, is unclear. We characterize the influence of the genetic background on peritoneal fibroproliferative tissue induced by sponge implants in DBA/1, Swiss, C57BL/6, and BALB/c mouse strains. In addition, responses to dipyridamole in the implants were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…These investigators observed highly variable responses among the four different groups of mice at 7 days following implantation. For example, angiogenesis and macrophage infiltration were greatest in C57BL/6 mice when compared with the other three inbred strains of mice [47]. Interestingly, fibrogenesis markers, as assessed by implant-derived transforming growth factor beta-1 and collagen were consistently lower in DBA/1 mice when compared with the other three inbred strains.…”
Section: Use Of Outbred Stocks To Study Inflammatory Diseasesmentioning
confidence: 94%
See 3 more Smart Citations
“…These investigators observed highly variable responses among the four different groups of mice at 7 days following implantation. For example, angiogenesis and macrophage infiltration were greatest in C57BL/6 mice when compared with the other three inbred strains of mice [47]. Interestingly, fibrogenesis markers, as assessed by implant-derived transforming growth factor beta-1 and collagen were consistently lower in DBA/1 mice when compared with the other three inbred strains.…”
Section: Use Of Outbred Stocks To Study Inflammatory Diseasesmentioning
confidence: 94%
“…Inflammatory angiogenesis Inflammation and angiogenesis are important physiological responses that are required for fibrovascular tissue growth and wound healing. However, dysregulation of this proliferative response may result in the development of chronic inflammatory diseases such as atherosclerosis, rheumatoid arthritis, asthma and inflammatory bowel disease, to name just a few [42][43][44][45][46][47]. Recent studies by Andrade and coworkers examined how host genetic diversity may influence the development and perpetuation of inflammatory angiogenesis and fibrogenesis.…”
Section: Use Of Outbred Stocks To Study Inflammatory Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are certainly genetic variations in vulnerability to fibrosis (Marques et al, 2014), but genetics are not the whole story. Epigenetics describes functional changes in genome activity while the genetic sequence remains unchanged.…”
Section: Epigenetic Factorsmentioning
confidence: 99%